Citrate synthase from Antarctic ciliates:adaptation to low temperatures and comparison with temperate ciliates - COPPELLOTTI, OLIMPIA; VANNUCCI D. (Polar Biology, 2003)
The activity of citrate synthase (CS), a mitochondrial enzyme in the energy metabolism pathway, was studied in Euplotes focardii (Hypotrichia) and Uronema marinum (Scuticociliatia), isolated from samples of Antarctic seawater and, for comparison in E. vannus and U. nigricans, related ciliates from the Adriatic. The temperature-dependent characteristics of CS were investigated in the range 0–55C, to evaluate mechanisms of thermal regulation, such as optimal temperature levels, activation energy, and kinetic parameters. CS activity was up to double that recorded in temperate organisms at reaction temperatures between 0 and 10C. The optimal temperature for enzymatic activity was independent of Tamb. Activation energy for CS was significantly lower in Antarctic ciliates than in temperate ones, indicating a significant increase in the reaction rate. KM at various temperatures of the reaction substrates indicated the higher affinity of CS for acetyl-CoA in both Antarctic organisms at lower temperatures. The data for thermal profiles for KM, showing greater differences between E. focardii and E. vannus than between U. marinum and U. nigricans, support the distinctive physiological characteristics of each species. E. focardii is an endemic and psychrophilic species, whereas U. marinum is a typically ubiquitous species, more adaptable to environmental changes.